Development of a global multistage reaction mechanism for fast pyrolysis of chlorella vulgaris microalgas anf its application in computational fluid dynamics simulations. - Mora Chandía, Tomás Guillermo (2018)
This document presents a research work on the mathematical modeling of the fast pyrolysis process of microalgae biomass by means of the construction of a reaction mechanism based on Arrhenius kinetic parameters. The interest in microalgae biomass as a source of bio-fuels and chemical products has grown only very recently from the last decade of the XX century. Although several papers related to the thermal decomposition of microalgae were found in the literature, only a few works are related to specific microalgae species. In particular, the microalgae species having more experimental data found in the literature was the Chlorella Vulgaris. Therefore, this species was chosen in this research in order to develop a reaction mechanism. Mathematical models for pyrolysis of lignocellulosic or woody materials have been developed for almost sixty years. Therefore, a large quantity of experimental data such as from the TG, DTG, DSC thermal analysis has been accumulated. As a consequence, sophisticated and comprehensive reaction mechanisms of pyrolysis have been developed. On the other hand, although the interest in the pyrolysis process about microalgae has grown, only a few works have reported thermal decomposition data, kinetic constants, products composition or complete reaction mechanisms in order to predict the devolatilization. As a consequence, there is currently no reaction mechanism coupled to CFD-type models that simulate rapid pyrolysis or devolatilization in reactors. In this context, this research proposes the development of a new multi-stage global reaction mechanism for the Chlorella Vulgaris species, based on the fundamental analysis TG and DTG and supported by well developed concepts, methodologies and principles for lignocellulosic biomass thermal analysis. The results obtained in this research have evidenced that the reaction mechanism has a very good agreement compared to experimental data of TG and DTG, accurately predicting the complex devolatilization of Chlorella Vulgaris in several steps. Following the objectives of this research, in a second stage, the set of chemical kinetic parameters were adapted to be used in a hydrodynamic numerical simulation (CFD). The adapted reaction mechanism was applied to simulating the devolatilization process in conjunction with a tubular fluidized reactor obtained from the literature which was used in studying the fast pyrolysis process of the Chlorella Vulgaris. In order to numerically solve the hydrodynamics and the rate equations, the finite volume method was used considering two Eulerian phases and an axis-symmetric domain. In particular, the solid phase, composed by the Chlorella Vulgaris powder was considered as a dispersed granular phase describing its rheology by means of the kinetic theory of granular flows. ANSYS Fluent 19.0 software package was used in defining and constructing the mesh and solving the set of discretized conservation equations using a transient pressure-based solver. Simulation using the adapted reaction mechanism for a reactor temperature of 673 K was performed for four different grid refinements in order to determine the solution convergence. Simulation results showed that the reaction mechanism can predict well the kinetics of the biomass conversion at high heating rates. Furthermore, and as expected, the results also showed that the biomass conversion depends strongly on the local temperature that is related to the granular rheology and transport processes of mass, momentum, and energy that have a fundamental role to control and to limit the overall biomass conversion.